Supplemental Material - Predictive value of adenoid-nasopharyngeal ratio in the diagnosis of secretory otitis media - Ping Li; Tao Li; Liang Yu; Aiping Chen; Yisha Wu; Yuzhu Wan; Li Shi (SAGE Journals, 2022)
Supplemental Material for Predictive value of adenoid-nasopharyngeal ratio in the diagnosis of secretory otitis media by Ping Li, Tao Li, Liang Yu, Aiping Chen, Yisha Wu, Yuzhu Wan and Li Shi in Ear, Nose & Throat Journal
Keywords: Otorhinolaryngology